Evaluating Risk Factors for Late-onset Neonatal Sepsis - Wedi Iskandar; Rizky Dwi Juniartho; Yani Triyani; Vidi Permatagalih (Global Medical & Health Communication (GMHC), 2025)
Abstract Late-onset neonatal sepsis (LONS) encompasses sepsis presenting ≥72 hours after birth, is commonly attributed to hospital-acquired infections, and contributes significantly to morbidity and mortality among newborns. The study aims to identify the risk factors associated with LONS. The study design was a retrospective, case-control observational study evaluating the medical records of neonates admitted to the neonatal care unit of Al Islam Hospital in Bandung from 2020 January 1 to 2022 December 31. This study assessed the impact of the following independent variables: gestational age (GA), birth weight (BW), mechanical ventilation, invasive procedures, total parenteral nutrition (TPN), and length of stay. Chi-square to bivariate and logistic regression to multivariate analyses were utilized to examine the data. In total, 85 infants were included in the study, 29 cases of LONS (34.1%). In the bivariate analysis, the occurrence of LONS based on BW (<1,500 grams), GA (<34 weeks), mechanical ventilator, invasive procedures, TPN, length of stay ≥10 days were (p=0.004, 95% CI=1.503 to 9.978, OR=3.872), (p=0.924, 95% CI=0.386 to 2.853, OR=1.050), (p=0.079, 95% CI=0.836 to 12.030, OR=3.171), (p=0.171, 95% CI=0.756 to 4.717, OR=1.888), (p=0.005, 95% CI=1.513 to 20.782, OR=5.608), (p=0.038; 95% CI=1.031 to 9.356, OR=3.106), respectively. In multivariate analysis, the risk factors were not significantly associated with p≥0.05, with a Nagelkerke R² of 0.365. In conclusion, BW<1,500 grams, TPN, and length of stay ≥10 days showed significant correlations with the occurrence of LONS, which increased by 36.5% when all variables were considered simultaneously.